Development of an analytical model for the dryout characteristic in helically coiled tubes. (1st May 2022) - Xu, Ziyi; Liu, Maolong; Chen, Cong; Xiao, Yao; Gu, Hanyang
Highlights: Experiment study of dryout characteristic in helically coiled tubes covers a wide range of system and geometric parameters. The dryout patterns are divided into three groups according to the distribution of the liquid film thickness. The effects of system and geometric parameters on the dryout quality and pattern are analyzed. A "dryout map" and the correlations of dryout quality are proposed and can accurately predict the dryout characteristics in helical coiled tubes. Abstract: In helically coiled tubes, the geometry-induced centrifugal force exerts upon the fluid to make the dryout phenomenon complicated. Hence, it is essential to understand the dryout mechanism and develop a model to accurately predict the dryout quality and dryout pattern in helically coiled tubes that can cover a wide range of parameters. In this paper, 17 helically coiled tubes with different coil diameters (160 ∼1350 mm), inner diameters (9 ∼14 mm) and inclined angles (2.5 ∼ 10°) are used to conduct the experimental study of the dryout characteristic under different conditions, including pressure between 2 and 7 MPa, mass flow rate between 100 and 1000 kg/(m 2 ·s), heat flux between 50 and 700 kW/m 2 . Three types of dryout patterns in helically coiled tubes were observed by analyzing the circumferential distribution of the wall temperature, including the gravity-dominated pattern, the secondary-flow-dominated pattern and the centrifugal-force-dominated pattern. Then the effects of the operational and geometric parameters of helically coiled tubes on the dryout characteristic have been studied, such as system pressure, mass flow rate, heat flux, tube diameter and coil diameter. Finally, a "dryout map" was developed based on the experimental data (297 data points), and an analytical model of dryout quality was proposed in terms of dimensionless groups for each zone. The correlations were verified by comparing with the experimental results in the open literature. The proposed correlations in this paper can give a better prediction for different experimental results.